Conceptual Design of a Pilot-Scale Pyroprocessing Facility. (4th May 2019) - Chang, Yoon Il; Benedict, Robert W.; Bucknor, Matthew D.; Figueroa, Javier; Herceg, Joseph E.; Johnson, Terry R.; Koehl, Eugene R.; Lell, Richard M.; Park, Young Soo; Pope, Chad L.; Wiedmeyer, Stanley G.; Williamson, Mark A.; et al.
Abstract: Argonne National Laboratory and Merrick & Company developed the conceptual design of a pilot-scale (100 T/year) pyroprocessing facility for the treatment of used fuel generated by commercial light water reactors and subsequent treatment of waste streams generated during the process. The primary purpose of this study was to perform sufficient engineering for the pilot facility conceptual design so that credible capital and operating cost estimates could be developed. Initial safety, safeguards, and security assessments were also completed to provide a detailed evaluation in these areas that can significantly affect both capital and operating costs. Electrorefining-based pyroprocessing resulted in a compact hot-cell facility with few process equipment systems. The process equipment and support systems were estimated to cost $93 million and the facility $305 million for a project total cost of $398 million. The annual operating cost was estimated at $53 million/year. Scaling up to a commercial-scale (400 T/year) was also evaluated and the capital cost was estimated at $911 million with annual operating cost of $90 million/year.